Investigation of vibration and surface roughness in micro milling of PMMA - Ali, Mohammad Yeakub; Mohamed, Abd. Rahman; Asfana, Banu; Roslan, Lutfi; Fahmi, M. I. (Trans Tech Publications Ltd., Switzerland, 2012)
This paper presents the vibration and surface roughness issue of poly methyl methacrylate (PMMA) workpiece produced by micro end milling using integrated multi-process machine tools DT 110 (Mikrotools Inc., Singapore) with control parameter; spindle speed, feed rate, and depth of cut. The vibration was measured using accelerometer, DYTRAN Instrument and the average surface roughness Ra was measured using Wyko NT1100. The optimum solution for minimum average vibration is 64.3 Hz with spindle speed 3000 rpm, feed rate 2 mm/min, and depth of cut 1.5 μm. However, the optimum solution for minimum average surface roughness, Ra is 0.352 μm with spindle speed 2000 rpm, feed rate 2 mm/min, and depth of cut 1.5 μm. The micro end milling parameters are suitable to machine PMMA to get good precision surface roughness. The analysis revealed that the feed rate and depth of cut is the most influential parameter on vibration during machining process meanwhile for average surface roughness, Ra spindle speed is the most influential parameter.